ENVIRONMENTAL AWARENESS AMONG SENIOR SECONDARY LEVEL STUDENTS (MAHESHWAR AND MANDLESHWAR. DIST. KHARGON (M.P.) - Jain, Ritesh (International Journal of Research -GRANTHAALAYAH, 2015)
Environment is, in general terms, a surrounding or condition influencing development and growth of all the living beings. For the last several decades nature and environment have always been a source of human reflection and investigation as the environmental pollution has reached to such a critical stage that we find ourselves passing through an irreversible climate change and are not able to retrieve the previous climate back. Now the liability lies on the next generation and I am sure that environmental awareness among the senior secondary students will lead the next generation towards restraining the unstoppable environmental changes. It can be said that environmental education is education through environment, about environment and for environment. It is both a style and subject – matter of education. In so far as the style is concerned, it means teaching for environment that include components and issues such as controlling the environment, establishing proper ecological equilibrium which entails proper use and conservation of resources and also involves control of environment is not only functionally useful but is also aesthetically enjoyable.